Effect of Salt on the Rheological Properties of Low-in-Fat O/W Emulsions Stabilised with Polysaccharides - Quintana, Juan Manuel (2002)
The droplet size distribution, stability, flow and viscoelastic properties of 35% oil-in-water emulsions stabilised with 1% w/w Tween 60 and: (i) 5% potato starch (PS), (ii) 5% potato starch and 0.5% xanthan gum (PS + XG), or (iii) 1% xanthan gum (XG), with and without the addition of 0.5M NaCl were studied. Visual inspection of the emulsions that contained XG and PS + XG, with and without NaCl, showed that they remained stable after 6 months. Emulsions stabilised with PS (without salt) showed an incipient interface after four months storage, while those containing 0.5 M NaCl destabilised within a month. The presence of NaCl did not affect droplet size distribution. Microscopic observations showed that all the emulsions flocculated. The rheological properties of these emulsions were characterised on a controlled-stress rheometer. The linear viscoelasticity was determined by oscillatory measurements that revealed the systems that exhibited weak gel-like properties. The addition of NaCl to the systems caused a decrease of viscosity, storage modulus and of loss modulus for emulsions containing PS and PS + XG while it did not affect emulsions prepared with XG alone. The viscoelastic linear behaviour was described according to the Maxwell generalised model and the discrete relaxation time spectra of the emulsions by means of the BSW-CW model.